The influence of Packed Cells Volume (PCV) and Temperature on Erythrocytes Sedimentation Rate (ESR) (Baghdad Science Journal, 2025)
Erythrocytes aggregation is an important physiological phenomenon in the circulation of blood, and is a basic characteristic of normal blood that plays a major role in cardiovascular system especially in the microcirculation.Blood samples have been taken from (30) volunteers (15 male, and 15 female), their ages (20-30) years. The Erythrocytes Sedimentation Rate (ESR) for those subjects was measured at different Packed Cells Volume (PCV) (10%-25%), and also it was measured at different temperature (10oC-25oC).The results show that there was a highly significant decrease (P